Supernova siblings and their parent galaxies in the Zwicky Transient Facility Bright Transient Survey. Issue 1 (6th January 2022) - Graham, Melissa L; Fremling, Christoffer; Perley, Daniel A; Biswas, Rahul; Phillips, Christopher A; Sollerman, Jesper; Nugent, Peter E; Nance, Sarafina; Dhawan, Suhail; Nordin, Jakob; Goobar, Ariel; Miller, Adam; et al.
ABSTRACT: Supernova (SN) siblings – two or more SNe in the same parent galaxy – are useful tools for exploring progenitor stellar populations as well as properties of the host galaxies such as distance, star-formation rate, dust extinction, and metallicity. Since the average SN rate for a Milky Way-type galaxy is just one per century, a large imaging survey is required to discover an appreciable sample of SN siblings. From the wide-field Zwicky Transient Facility (ZTF) Bright Transient Survey (which aims for spectroscopic completeness for all transients which peak brighter than r < 18.5 mag) we present 10 SN siblings in five parent galaxies. For each of these families, we analyse the SN's location within the host and its underlying stellar population, finding agreement with expectations that SNe from more massive progenitors are found nearer to their host core and in regions of more active star formation. We also present an analysis of the relative rates of core collapse and thermonuclear SN siblings, finding a significantly lower ratio than past SN sibling samples due to the unbiased nature of the ZTF.